FROM NORMATIVE COMMITMENT TO EFFECTIVE ACCOUNTABILITY: RECONSTRUCTING STRUCTURAL REMEDIES FOR CORPORATE CRIMINAL LIABILITY IN INDONESIA - Tumian Lian Daya Purba; Silvester Magnus Loogaman Palit; Ali Rahman; Yassine Chami (KANUN:JURNAL ILMU HUKUM, 2026)
Indonesia’s corporate criminal liability has transitioned from fragmented sectoral laws to general codification under the New Criminal Code (Law 1/2023) and Law 1/2026. Despite this legal context, a significant legal gap remains: a persistent "operational deficit" leading to systemic under-enforcement. Standard fines are frequently internalized as business costs, while law enforcement remains "actor-centered," prioritizing individual executives over the criminogenic corporate architecture. This study addresses the central question of how to reconstruct the Indonesian liability regime to move from formal normative commitment to effective, practical accountability. Employing normative juridical methods with statutory, conceptual, and comparative approaches, the research analyzes attribution models and restorative justice mechanisms. Findings indicate that effective accountability requires a shift toward an organization-centered model that targets internal governance. Proposed reforms include structural remedies, such as compliance-based corporate probation, disgorgement of unlawful gains, and mandatory ecological restoration, implemented through a "Dual Track System". Furthermore, this article highlights the necessity of procedural innovations like Deferred Prosecution Agreements (DPAs) and the enforcement of successor liability to prevent impunity during corporate restructurings. This article contribute  to prescriptive ius constituendum model that links corporate fault to proportional, remedial sanctions. By addressing inherent power imbalances and refining technical attribution standards, this framework provides a pathway for Indonesia to achieve a practically deterrent and restorative corporate liability regime.